Influence of Non-genetic Factors on Pre-weaning Survivability of Lambs in Three North-Western Districts of Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
The productivity as well as earnings from a lamb farm largely depends on the pre-weaning survivability of lamb. This study was intended to assess the factors affecting pre-weaning survivability of lamb in field conditions. Data from a total of 133 lambs produced from 82 mother ewes was collected from beneficiary farmers of three North-western districts (Gaibandha, Bogura, and Rajshahi) of Bangladesh. Various non-genetic factors i.e. dam age, suckling, mothering behavior, sex, birth weight (g), body condition score (BCS), types of birth were determined form birth to weaning. The results showed that the overall survivability was 92.5% and 94.3% for birth to seven days and eight days to weaning, respectively. The survival percentages of young sheep in birth to seven days was significantly affected (p < 0.05) by the suckling, mothering behavior, birth weight (kg), BCS and type of birth. The highest survivability was observed for those lamb who had age of 4 yrs (96.6%), suckled for several times (96.9%), provided with good mothering behavior (98.7%), had birth weight in between 1 and 2 kg (97.5%), BCS more than 3 (97.3%) and twin born (95.2%). Whereas, dam age (4 yrs; 98.2%), suckling (twice; 98.8%), mothering behavior (Good; 97.5%), birth weight(>1 kg; 98.7%) greatly responsible for lamb survival in eight days to weaning stages (p < 0.05).In addition, the sexes of lamb found no significant relationship (p > 0.05) in terms of survivability during pre-weaning stages. Therefore, it could be said that dam age, suckling, mothering behavior and birth weight help to increase lamb survivability at pre-weaning stages.J Bangladesh Agril Univ 23(1): 93–98, 2025